Simulation and Modelling of Hydrogen Production Process using Proton Exchange Membrane and Alkaline Electrolysis- A review. (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
This review provides a comprehensive analysis of modelling approach for hydrogen production processes employing Proton Exchange Membrane (PEM) and Alkaline Electrolysis technologies, implemented using MATLAB Simulink/Simscape. The systematic review revealed that for PEM electrolysis, emphasis is placed on intricate modelling of system components crucial for hydrogen production, transient responses, and the integration with renewable energy sources like photovoltaic modules. Conversely, studies on Alkaline electrolysis delve into the influence of structural parameters, operating conditions, efficiency and hydrogen production rates. By comparing and contrasting these approaches, the review elucidates the strengths and limitations of each methodology and their contributions to advancements in renewable energy-based hydrogen production systems. Furthermore, the review discusses future research directions and potential areas for optimisation and innovation in hydrogen production plant modelling using MATLAB Simulink/Simscape. This review identifies gaps in current research and proposes potential avenues for future investigation, with the aim of advancing our understanding and optimisation of hydrogen production process for a sustainable energy future.
Keywords: Simulink; Electrolysers; Green Hydrogen; Clean Technology.